The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1099/00221287-145-12-3365
|View full text |Cite
|
Sign up to set email alerts
|

Intermediates of rifamycin polyketide synthase produced by an Amycolatopsis mediterranei mutant with inactivated rifF gene

Abstract: Rifamycin B biosynthesis in Amycolatopsis mediterranei N/813 was inactivated by introducing a small deletion in the rifF gene situated directly downstream of the rifamycin polyketide synthase (PKS) gene cluster. The corresponding mutant strain produced a series of linear intermediates of rifamycin B biosynthesis that are most probably generated by obstruction of the normal release of the end product of the rifamycin PKS. This result provides evidence that the rifF gene product catalyses the release of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 26 publications
(27 reference statements)
2
46
1
Order By: Relevance
“…However, mutant strain MT0031ABH, in which a 21 kb fragment of the post-PKS modification genes has been deleted, did not accumulate proansamycin X, but instead the tetraketides SY4b and desacetyl-SY4b were produced. These compounds have previously been isolated from knock-out mutants of the amide synthase RifF, as a result of premature release of the polyketide chain intermediates from the enzyme, starting from the tetraketide through the undecaketide (Stratmann et al, 1999;Yu et al, 1999). Structure identification of these intermediates showed that from the pentaketide onwards they contain a naphthalene ring, suggesting that the formation of the naphthalene moiety of rifamycin B takes place during the chain extension of the polyketide, specifically between the tetraketide and the pentaketide stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, mutant strain MT0031ABH, in which a 21 kb fragment of the post-PKS modification genes has been deleted, did not accumulate proansamycin X, but instead the tetraketides SY4b and desacetyl-SY4b were produced. These compounds have previously been isolated from knock-out mutants of the amide synthase RifF, as a result of premature release of the polyketide chain intermediates from the enzyme, starting from the tetraketide through the undecaketide (Stratmann et al, 1999;Yu et al, 1999). Structure identification of these intermediates showed that from the pentaketide onwards they contain a naphthalene ring, suggesting that the formation of the naphthalene moiety of rifamycin B takes place during the chain extension of the polyketide, specifically between the tetraketide and the pentaketide stage.…”
Section: Discussionmentioning
confidence: 99%
“…Based on results of the present study and others (Stratmann et al, 1999;Yu et al, 1999), it was clear that the core naphthalene ring moiety of rifamycin is constructed during the polyketide chain extension process. However, the fact that the reaction may require a catalytic enzyme, whose gene is located in the post-PKS modification region and functions in trans with the PKS, is rather unusual.…”
Section: Inactivation Of Rif-orf3mentioning
confidence: 99%
See 2 more Smart Citations
“…The AT domain of module 3 of AsmB, which is predicted to recognize the ''glycolate'' extender unit, shows no unusual sequence signature that would distinguish it from other AT domains. Located immediately downstream of asmD is asm9, which encodes a protein with a high degree of similarity to RifF, the chain-terminating, cyclizing enzyme of rifamycin biosynthesis (33,34). It is proposed that the C terminus of the fully extended polyketide chain is transferred from AsmD to the conserved Cys-73 on the Asm9 protein, followed by intramolecular amide bond formation with the aromatic amino group to release a 19-membered macrocyclic lactam, proansamitocin (Fig.…”
Section: Identification and Cloning Of The Ansamitocin Biosynthetic Genementioning
confidence: 99%